Penerapan Koperasi Menurut KH Abdul Wahab Chasbullah - Asyari Hasan; Nadhil Novarel Mathari (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This study aims to reveal the role of KH. Abdul Wahab Chasbullah as a figure who played a role in realizing Nadlatul Tujjar and also the Al-inan Syirkah Cooperative. The problems investigated in these writings are in several ways, namely the background of KH's life. Abdul Wahab Chasbullah, the efforts of KH. Abdul Wahab Chasbullah in the Nadlatul whatan, Nadlatul Afkar and Nadlatul Tujjar organizations and the influence of KH. Abdul Wahab Chasbullah towards society in economic, political and social terms. To examine these problems, this study uses a literature review method to reveal historical facts about the role of KH. Abdul Wahab Chasbullah in Nadhlatul Tujjar. To analyze these facts, the researcher used an observational approach, interviewed historians and also looked at existing books and journal articles. This study found that KH. Abdul Wahab Chasbullah was born in Tambakrejo Village, Jombang in March 1888 and died on December 29, 1971. Based on his lineage, Kiai Wahab Hasbullah, namely Kiai Said, is a kiai who is still a descendant of Sunan Pandan Arang Semarang. Born and raised in a pesantren environment, Mbah Wahab did grow up with strong pesantren values and character. Even at the age of 13, he has started his odyssey from one pesantren to another. Even after being satisfied with studying in Indonesia, he settled in Mecca to study knowledge from various well-known kiai. Nahdhatut Tujjar was founded by KH. Wahab Chasbullah in 1918 to fix the economy of Muslims on greed and monopolized by the Colonialism. The spirit of the Nahdhatul Tujjar movement is that Muslims do not always depend on their economy under the pressure of colonialism, besides that Muslims are also taught to be independent in the economy.